Effect of Skills Competency-Based Orientation on Clinical Performance Among Nursing Interns at University of Lahore Teaching Hospital: Effect of Skills Competency on Clinical Performance - Parveen , Razia; Ali, Afsar; Sarwar, Hajra; Aziz, Zunaira (Pakistan Journal of Health Sciences, 2023)
The competencies of nursing interns have direct effects on the wellbeing and health of patients, and lack of it can result in severe problems for the patients. Thus, the clinical performance and competence of nursing interns are the main professional and corporate problems for nurses and patients. Furthermore, it is needed that the nurses show the capability to supply quality care for patients and to collaborate with other nurses and colleagues. Objective: To determine the effect of skills Competency- based orientation on clinical performance among nursing interns at University of Teaching Hospital Lahore. Methods: A quasi experimental study design was used to conduct this study at University of Lahore Teaching Hospital among nursing interns. A simple random sample of n=40 participants was recruited. The educational intervention consisted of 12 sessions of 40 to 50 minutes each, from June, 2022 to August 2022.To collect data, permission was granted from the Research Ethical Committee (REC) and then Medical superintendent of University of Lahore Teaching Hospital. To assess the performance among nursing interns, an observational checklist was used. Data of the study participants were entered in statistical software SPSS 21.0 and was analyzed accordingly. Results: Findings revealed a significant effect of the educational intervention program on performance of nursing interns (Pre interventional performance score 21.00 +5.088and post interventional performance score 38.00+4.481among the nursing interns (p- value <0.001). Conclusion: It is concluded that nursing education program has effect on performance among nursing interns.